The prevalence of subclinical hypothyroidism among patients with diabetes mellitus at the Kalafong Hospital Diabetes Clinic : a cross-sectional study : original research - Van Zyl, D.G.; Ueckermann, V. (JEMDSA : the journal of endocrinology, metabolism and diabetes of South Africa, 2013)
Objective : The purpose of this study was to determine the prevalence of subclinical hypothyroidism among patients with diabetes mellitus at the Kalafong Diabetes Clinic in Pretoria. Design : Cross-sectional study. Setting and subjects : Five hundred and sixty-five patients with diabetes mellitus (type 1, type 2 or unknown), who were following-up at the Kalafong Hospital Diabetes Clinic. Outcome measures : The thyroid stimulating hormone (TSH) levels of patients were evaluated. Patients with TSH levels > 5.66 IU/ml (upper reference limit of the Kalafong National Health Laboratory Services laboratory) subsequently underwent repeat thyroid function evaluation, including T4 level, to determine the prevalence of subclinical hypothyroidism. Results : A total of 563 patients met the inclusion criteria for this study and underwent TSH evaluation. The prevalence of subclinical hypothyroidism was found to be 0.9% in the study population, and 1.6% in a subgroup of patients with type 2 diabetes mellitus. Conclusion : The prevalence of subclinical hypothyroidism in this South African population of patients with diabetes was significantly lower than that stated in the literature. This holds true for both the general population and populations of patients with diabetes mellitus. To our knowledge, there is no data available for the prevalence of subclinical hypothyroidism in the general population in South Africa for comparison with the study group.